Pathogenic conversion of Foxp3+ T cells into TH17 cells in autoimmune arthritis - Komatsu, Noriko; Okamoto, Kazuo; Sawa, Shinichiro; Nakashima, Tomoki; Oh-hora, Masatsugu; Kodama, Tatsuhiko; Tanaka, Sakae; Bluestone, Jeffrey A; Takayanagi, Hiroshi (Nature medicine, 2014)
Regulatory T (T reg ) cells exhibit substantial phenotypic and functional plasticity. Hiroshi Takayanagi and his colleagues report that in autoimmune arthritis, a subset of T reg cells can lose Foxp3 expression and convert into T H 17 cells. This conversion is mediated by synovial fibroblast-derived IL-6, and in vivo , these cells are osteoclastogenic and exacerbate arthritis. These findings suggest that a proportion of pathogenic T H 17 cells in autoimmune disease may be derived from T reg cells. Autoimmune diseases often result from an imbalance between regulatory T (T reg ) cells and interleukin-17 (IL-17)-producing T helper (T H 17) cells; the origin of the latter cells remains largely unknown. Foxp3 is indispensable for the suppressive function of T reg cells, but the stability of Foxp3 has been under debate. Here we show that T H 17 cells originating from Foxp3 + T cells have a key role in the pathogenesis of autoimmune arthritis. Under arthritic conditions, CD25 lo Foxp3 + CD4 + T cells lose Foxp3 expression (herein called exFoxp3 cells) and undergo transdifferentiation into T H 17 cells. Fate mapping analysis showed that IL-17–expressing exFoxp3 T (exFoxp3 T H 17) cells accumulated in inflamed joints. The conversion of Foxp3 + CD4 + T cells to T H 17 cells was mediated by synovial fibroblast-derived IL-6. These exFoxp3 T H 17 cells were more potent osteoclastogenic T cells than were naive CD4 + T cell–derived T H 17 cells. Notably, exFoxp3 T H 17 cells were characterized by the expression of Sox4, chemokine (C-C motif) receptor 6 (CCR6), chemokine (C-C motif) ligand 20 (CCL20), IL-23 receptor (IL-23R) and receptor activator of NF-κB ligand (RANKL, also called TNFSF11). Adoptive transfer of autoreactive, antigen-experienced CD25 lo Foxp3 + CD4 + T cells into mice followed by secondary immunization with collagen accelerated the onset and increased the severity of arthritis and was associated with the loss of Foxp3 expression in the majority of transferred T cells. We observed IL-17 + Foxp3 + T cells in the synovium of subjects with active rheumatoid arthritis (RA), which suggests that plastic Foxp3 + T cells contribute to the pathogenesis of RA. These findings establish the pathological importance of Foxp3 instability in the generation of pathogenic T H 17 cells in autoimmunity.